Secondary amputation: a qualitative study of quality of life in patients after primary limb salvage surgery and after later ablative sarcoma treatment - Veronika Vetchy; Carmen Trost; Reinhard Windhager; Gerhard Hobusch (Journal of Rehabilitation Medicine)
Objective: This study focuses on how patients experience the time following amputation after primary limb salvage surgery due to musculoskeletal malignancies. Limb salvage is state of the art in the treatment of musculoskeletal tumours. Nonetheless, in some cases, limb salvage can become problematic over time, resulting in poorer limb function and septic outcomes. This raises the question of whether amputation is indicated sooner rather than later. Patients who have undergone secondary amputation might retrospectively prefer a different approach.